US interests in Haiti: a background paper for the Caribbean/Latin American Action Conference, Miami, Florida - Preeg, Ernest H. (Centre for Strategic and International Studies WashingtonUS, 1993)
Highlights the three circumstances that have made Haiti become an important interest to the United States viz: illegal migration/refugee inflow; deep ties and integration between Haitians and the Afro American community; and, the 1991 OAS commitment to restore democratically elected governments deposed by the military.